Robert Lowell in a new century : European and American perspectives - Austenfeld, Thomas, 1960- (Studies in American literature and culture., 2019)
"Robert Lowell (1917-1977) holds a place of unchallenged prominence in the poetic pantheon of the twentieth-century United States. He is an essential focal point for understanding the connection between poetry and American history, social justice, and personal identity. A recent spate of publications both by and about him, as well as allusions to him in the work of major American poets such as Wanda Coleman and Claudia Rankine, attest to his continued relevance. In March 2017, leading Lowell scholars from Europe and America gathered at the University of Fribourg, Switzerland in commemoration of his 100th birthday. The essays deriving from the conference and presented here after careful revision reveal new aspects of Lowell: for instance, the poet's influence on his peers, discussed by Thomas Travisano, the biographer of Elizabeth Bishop; or echoes of Milton in Lowell's work, discussed by Saskia Hamilton, editor of the forthcoming Dolphin Letters between Lowell and Elizabeth Hardwick. Other essays examine Lowell's struggles with bipolar illness, with marriage, and with money; his economic views and his early personality issues with respect to his poetic production; his extended sojourn in Amsterdam; and his special relationship with Ireland. Several essays focus on his 1961 volume Imitations, his major poetic engagement with the European tradition, unjustly neglected in the US. The essays will appeal to the wide audience that Lowell scholarship continues to command"--